2019
DOI: 10.1007/s11164-019-04003-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecules and heterostructures at TiO2 surface: the cases of H2O, CO2, and organic and inorganic sensitizers

Abstract: TiO2-based (nano)materials are widely exploited in systems and devices of actual technological interest, because of their outstanding physical and chemical properties, including chemical stability, long durability, non-toxicity abundance and low cost. For this, they are considered ideal for many practical applications including energy-related devices, photocatalysis, but are known to have some limitations. To improve their performance and then to find more efficient materials in the energy and environmental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…The fact that molecular adsorption of H2O is favored over dissociative adsorption on a defect-free anatase (101) facet has already been described in the literature. [106][107][108][109] In a first step, the impact of a single H2O molecule (i.e. a monohydrated 22 surface) is evaluated.…”
Section: Impact Of Hydrated Anatase (101)mentioning
confidence: 99%
“…The fact that molecular adsorption of H2O is favored over dissociative adsorption on a defect-free anatase (101) facet has already been described in the literature. [106][107][108][109] In a first step, the impact of a single H2O molecule (i.e. a monohydrated 22 surface) is evaluated.…”
Section: Impact Of Hydrated Anatase (101)mentioning
confidence: 99%
“…Although the structure of the surface can be investigated by using microscopy techniques, including electron and scanning tunneling microscopies, details concerning the surface sites of TiO 2 polytypes still remain elusive. In general, an accurate and deep understanding of the active sites, their Lewis acidity, coordination states, including local defects and more extended terminations at the surface, can be gained by adsorption of small molecular probes (Mino et al, 2014(Mino et al, , 2019Zaera, 2014;Cravanzola et al, 2017), like CO (Desjonqueres and Spanjaard, 1996;Hadjiivanov and Klissurski, 1996;Scarano et al, 2004;Groppo et al, 2006). In this contest, we report a Fouriertransform infrared (FTIR) spectroscopic study of the surface sites present on TiO 2 P25 treated at different temperatures (RT,473,673,773,873,973, and 1,023 K) or etched with HF solutions at different level of concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, bicarbonate and carbonated anions, similarly to The occurrence of brookite as the prevalent phase immediately after the purification step can be ascribed to a high stochiometric excess of bicarbonate and carbonate anions present in the reaction medium with respect to the TiO 2 precursor (approximately 5:1 according to the investigated experimental condition). Under these conditions, bicarbonate and carbonated anions, similarly to oxalate anions, can act as rigid bidentate ligands [26,27], able to bridge two Ti centers, thus leading to a chelate complex that promotes the stabilization of the oxide, namely the metastable brookite phase, as previously reported [28]. Several reports, indeed, indicated that brookite generation takes place through the formation of water-soluble titanium complexes including oxalates [28], citrates [29] and lactates [30].…”
Section: Sample Name Size (Nm)mentioning
confidence: 58%
“…HRTEM analyses do not allow to us distinguish between the anatase and brookite phases, due to both the inherent accuracy of magnification calibration in HRTEM, not higher than 5% [26], and the similarity of the two polymorphs of TiO 2 , that share the octahedral coordination of Ti atoms but slightly differ in the way the TiO 6 octahedra are linked [27]. For this reason, the indexing of the fast Fourier transforms (FFTs) of HRTEM images in Figure 5 is done based on both phases. )…”
Section: Sample Anatase Phase Brookite Phasementioning
confidence: 99%